0862 A unique case of severe sleep onset and maintenance insomnia following COVID-19 vaccination. (25th May 2022) - Aryal, Shubekchha; Kramer, Joshua; Azzouz, Mouhannad; Stansbury, Robert
Abstract: Introduction: The COVID-19 vaccines have documented transient side effects, including injection site soreness, redness, headache, fatigue, and fever. In addition, there have been few reported long-term side effects, including Guillain-Barre, pericarditis, and cerebral venous sinus thrombosis. We present a rare case of severe insomnia as a long-term side effect following COVID-19 vaccination. Report of Cases: A 59-year-old female with a past medical history of well-controlled hypothyroidism and migraine presented to the sleep center with four months of insomnia. She had a history of COVID infection in November 2020 with only mild symptoms of sore throat and fatigue. The patient finished her two-shot series of the Moderna COVID-19 vaccine in April 2021. Immediately following the vaccination, the patient had severe trouble falling and staying asleep. Her insomnia was resistant to multiple medications including zolpidem Immediate-release(IR), Controlled-release(CR) formulas, zaleplon, eszopiclone, trazodone, melatonin, clonazepam, suvorexant, and lemborexant. However, magnetic resonance imaging (MRI) brain imaging only showed nonspecific white matter disease. She had no mood disorders or psychosocial stressors, and the patient had excellent sleep hygiene measures. However, insomnia caused severe impairment of her daily life activities to a point where she was almost seeking inpatient admission for her insomnia. During the COVID-19 pandemic, the effects on sleep have been significant, particularly insomnia. Prescriptions for sleep medications have increased. Many have attributed the rise of insomnia to pandemic-related stress, disturbance of circadian rhythm from home confinement, and worsening mental health. Conclusion: To our knowledge, there have not been documented side effects of insomnia on the COVID-19 vaccines, with some studies suggesting sleep deprivation reducing their effectiveness. As vaccination efforts continue worldwide, awareness of side effects from vaccines is paramount for clinicians facing the challenges in patient care.This case demonstrates that chronic insomnia can be a side effect of the COVID-19 vaccines. Therefore, further surveillance of patients and side effects from COVID-19 vaccination is warranted as insomnia can have significant clinical and psychosocial consequences. Support (If Any):